Energy aware resource management in 6G IoT networks using STAR RIS - Ali Alqahtani; Neeti Taneja; Ashu Taneja; Nayef Alqahtani (Scientific Reports)
Abstract The massive IoT sensors, edge devices, software systems and the communication networks require a lot of computing resources for real-time data acquisition and analytics. This puts huge burden on the carbon footprint and energy consumption. To achieve carbon neutrality it is important to design energy aware solutions for sustainable computing. This paper presents a sustainable sixth generation (6G) communication framework supported with simultaneous transmission and reflection (STAR) reconfigurable intelligent surfaces (RISs). The STAR RISs introduce efficient power control by enabling wireless devices to operate at lower power levels. This in turn leads to huge energy savings and extends the battery life of devices. Further, the paper proposes a resource scheduling algorithm which enables association of computing resources, viz., user nodes and STAR-RISs. The system spectral efficiency and energy efficiency is evaluated for different RIS elements N and transmit power levels $$P_{max}$$ . It is observed that there is a gain of 8.92% in spectral efficiency and 13.9% in energy efficiency with the proposed association scheme involving STAR RIS. The STAR-RIS aided system outperforms the conventional RIS system by 5.26% at $$P_{max}$$ of 30 dBm. The comparison with the two baseline approaches offering random association and no association is also carried out. In the end, the practical applications of STAR-RIS aided IoT communication network are presented.